Targeted Enrichment of Enzyme‐Instructed Assemblies in Cancer Cell Lysosomes Turns Immunologically Cold Tumors Hot. (17th November 2021) - Ji, Shenglu; Li, Jun; Duan, Xingchen; Zhang, Jingtian; Zhang, Yufan; Song, Mengqing; Li, Songge; Chen, Hongli; Ding, Dan
Abstract: Lysosome‐relevant cell death induced by lysosomal membrane permeabilization (LMP) has recently attracted increasing attention. However, nearly no studies show that currently available LMP inducers can evoke immunogenic cell death (ICD) or convert immunologically cold tumors to hot. Herein, we report a LMP inducer named TPE‐Py‐pYK(TPP)pY, which can respond to alkaline phosphatase (ALP), leading to formation of nanoassembies along with fluorescence and singlet oxygen turn‐on. TPE‐Py‐pYK(TPP)pY tends to accumulate in ALP‐overexpressed cancer cell lysosomes as well as induce LMP and rupture of lysosomal membranes to massively evoke ICD. Such LMP‐induced ICD effectively converts immunologically cold tumors to hot as evidenced by abundant CD8 + and CD4 + T cells infiltration into the cold tumors. Exposure of ALP‐catalyzed nanoassemblies in cancer cell lysosomes to light further intensifies the processes of LMP, ICD and cold‐to‐hot tumor conversion. This work thus builds a new bridge between lysosome‐relevant cell death and cancer immunotherapy. Abstract : We report an alkaline phosphatase (ALP)‐responsive lysosomal membrane permeabilization (LMP) inducer, which can specifically accumulate in cancer cell lysosomes for evoking immunogenic cell death (ICD) and converting immunologically cold tumors into hot tumors.